Platelet-released ADP stabilizes PAF-induced rabbit platelet aggregation by stabilizing intracellular calcium - Yi Fu-Xian; Guo Zhao-Gui (Acta Pharmacologica Sinica; Vol 19, No 4 (July 1998): Acta Pharmacologica Sinica, 2016)
AIM: To examine whether platelet-released adenosine diphosphate (ADP) would contribute to the stabilization of rabbit platelet aggregation induced by platelet activating factor (PAF). METHODS: Rabbit platelet aggregation induced by PAF was measured turbimetrically. ADP release from rabbit platelets stimulated by PAF was determined by HPLC. Intracellular Ca2+ was measured using Ca(2+)-sensitive fluorescent indicator Fura 2-AM. RESULTS: PAF > or = 1 nmol.L-1 induced full platelet aggregation, which did not deaggregate over 5 min after aggregation reached peak. Platelet aggregation was deaggregated in a concentration-dependent manner by subsequent addition of ADP scavenger ATP-diphosphohydrolase (apyrase) at 5-100 mg.L-1. PAF 3 nmol.L-1 stimulated release of ADP (29% vs 6% of control), and elicited a rapid rise in intracellular calcium ([Ca2+]i) which peaked at approximately 15 s. Then the [Ca2+]i gradually decayed from 585 +/- 80 nmol.L-1 within 100 s to a low level (364 +/- 82 nmol.L-1). Apyrase 100 mg.L-1, added 2 min after PAF, reduced [Ca2+]i to a lower level (171 +/- 29 nmol.L-1). CONCLUSION: Platelet-released ADP stabilizes PAF-induced rabbit platelet aggregation by stabilizing [Ca2+]i at elevated level.